Determinants of Residential Property Price in Selected Asian Countries: A Sys-GMM Approach - Abasimi, Ignatius; Nabila, Alfira; Ramdhan, Muhammad Arsy; Anam, Muhammad Syariful (Universitas Ahmad Dahlan, Yogyakarta, 2025)
This study analyzes the determinants of residential property prices in 13 selected Asian countries. Key variables include the residential property price index, GDP per capita reflecting economic conditions, real interest rates impacting borrowing costs, inflation affecting purchasing power), population growth influencing housing demand, energy consumption reflecting demand pressures, and the Gini Index measuring income inequality. The research employs the System Generalized Method of Moments (Sys-GMM) for dynamic analysis of these endogenous variables. The results indicate that property prices are significantly influenced by prior price levels. Furthermore, GDP per capita, inflation, and population growth positively affect property prices, underscoring the roles of economic growth and demographic factors in shaping the property market. Higher GDP growth enhances household purchasing power, while population growth increases housing demand. Conversely, energy consumption negatively impacts property prices, reflecting cost pressures from rising energy demand. Interestingly, the real interest rate and Gini index do not significantly influence residential property prices, suggesting these factors may not directly affect price dynamics in the studied countries. These findings emphasize the need for policies that support economic stability and sustainable growth to enhance property market competitiveness. Policymakers should prioritize energy efficiency and inclusive economic development to ensure long-term resilience in the property sector. Sustainable economic policies are essential to strengthen the region's property market and effectively manage growing energy demands.